METABOLISME KARBON DALAM SIMBIOSIS FUNGI MIKORIZA ARBUSKULA - Hidayat, Cecep (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2012)
Arbuscular Mycorrhizal Fungi is a form of siymbiotic mutualism between fungi and plant root. Fungi give nutrients and water to host plant and host plant give carbon to fungi. Around 4 – 20 % photosynthate as hexose are translocated to mycorrhizal root and converted directly to glycogen and trehalose at IRM to continue transport to ERM. Carbon metabolism is going at asymbiotic and symbiotic phase with pathways consist of glycolysis, tricarboxilate acid cycle, and pentose phosphate pathway (PPP), glyoxilate, non photosynthesis carbon metabolism, and Glu and Arg synthesis. There is no lipid acid synthesis at asymbiotic phase so the fungi not produce new propagule and became symbion obligate. Carbon as TAG is synthesed at IRM and transported to ERM to preserve and used in ERM anabolism and spore germination. Carbon is transported through lipid translocation mechanism.